PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA GURU PONDOK PESANTREN AL USWAH PEKANBARU RIAU - DEHOTMAN, KHORNELIS (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
The study was conducted at islamic boarding school Al Uswah of Pekanbaru. In analyzing data obtained from research objects using descriptive and quantitative methods, descriptive is to compare between actual facts with theories that have to do with problems in order to draw conclusions and tabulated in the form of tables and then analyzed according to research and quantitative objectives using statistical tools simple linear regression method to determine the relationship between the dependent variable (Y) with one independent variable (X).Then based on the test results on the work environment variable (X), using SPSS assistance obtained thitung of 6,830-. then compared to the table at a significant level a = 5%, which is equal to 2,036 can be seen that the t-count is greater than the table (6,830> 2,036). Thus it can be concluded that the variable X (work environment) significantly influences the performance of the teachers islamic boarding school Al Uswah of Pekanbaru. While the value of R. Square (R2) of 0.593 (59.30%) explains that the work environment influences the performance of islamic boarding school Al Uswah Pekanbaru amounted to 59.30%. While the remaining 40.70% depicts other independent variables not observed in this study